The effect of lactation stage on milk composition of goat raised by farmers in Sleman Yogyakarta - Suranindyah, Yustina Yuni; Nurliyani, Nurliyani; Priyadi, Dwi Ahmad; Azizah, Siti Muniroh Nur (2014)
The purpose of study was to find out the effect of lactation stage on goat milk composition. Milk sample was taken from 22 Etawah crossbred goats with different stage of lactation, which was 1st, 2nd, 3rd, 4th, 5th and 6th month after kidding. Chemical analyses were conducted by measuring specific gravity, dry matter, fat, protein and ash content of milk. Mean of milk components were calculated and compared against stages of lactation. Results of this study showed that lactation of Etawah crossbred goats lasted for 5 to 7 months. Total solid, fat and protein content in milk of goat during the 2nd month of lactation were higher than that of in the 1st month (P<0.05). From 3rd month to the end of lactation mean of total solid, fat and protein content were not significantly different. There were also no different for milk gravity and ash content of milk in each lactation stages. The comparation among total solid, fat and protein contents in milk of the 1st, 2nd and 6th of lactation were 1.020; 2.32%; 3, 33% compared to 1.021; 4.83%; 4.87% and 1.027; 5.50%; 4.86%. The conclusion of study was milk of Etawah crossbred goat in the 1st month of lactation has lower content of total solid, fat and protein than that in the later stage of lactation.